A discussion of political influence on the operation of management accounting in organizations - Arifin Sabeni (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 1999)
Traditionallay, management accounting system can provide useful information to management for making decisions about the future of the organization and for controlling the implementation of the decisions they make. therefore, under traditional perspective, management accounting is seen as a technical and neutral information service for decision-making. This perceptions and societies are essentially stable. But, in fact, people in an organization are not passive objects, they have different types of roles, personalities, cognitive styles, and social background.